2013
DOI: 10.1103/physrevc.88.024303
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of neutron-rich Te and Xe isotopes within a new shell model context

Abstract: Te and Xe isotopes above the N = 82 shell closure are investigated within a large-scale shell model approach based on an iterative matrix diagonalization algorithm. The spectra and transition strengths, computed using a realistic Hamiltonian, are in overall agreement with the available experimental data. The calculation predicts an increasing neutron weight in the lowest collective 2+ 1 state of the isotopes as they depart from the doubly magic 132Sn and move toward the neutron drip line. Such a neutron domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
26
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 68 publications
6
26
0
Order By: Relevance
“…This is quite a striking result that is not expected by the present theoretical, or empirical predictions, for instance, see Ref. [24] in which 140 Te was described like a triaxial rotator with R = 2.33. The characteristics in the R systematics are as follows: for Te there is little difference in the R values, giving R ~ 0; for Sn, the differences are constant at R ~ -0.175; for Xe and Ba, the values split into three regimes; positive, close to zero, and negative; for Ce ( Z = 58) to Dy ( Z = 66) the lines have two branches which extend into the negative region, and, finally, for N = 88 there is a distinctive peak at Z = 56 and a pronounced valley at Z = 64.…”
supporting
confidence: 45%
See 1 more Smart Citation
“…This is quite a striking result that is not expected by the present theoretical, or empirical predictions, for instance, see Ref. [24] in which 140 Te was described like a triaxial rotator with R = 2.33. The characteristics in the R systematics are as follows: for Te there is little difference in the R values, giving R ~ 0; for Sn, the differences are constant at R ~ -0.175; for Xe and Ba, the values split into three regimes; positive, close to zero, and negative; for Ce ( Z = 58) to Dy ( Z = 66) the lines have two branches which extend into the negative region, and, finally, for N = 88 there is a distinctive peak at Z = 56 and a pronounced valley at Z = 64.…”
supporting
confidence: 45%
“…The discrepancy was explained by the quasiparticle random phase approximation as a neutron-pairing reduction [22] and by the Monte Carlo Shell Model as neutron dominance through asymmetric proton-neutron couplings [23]. Furthermore, a large scale shell model calculation also pointed out the importance of the neutron dominance in the wave function of excited states in neutronrich Te isotopes [24]. A recent study [8] showed that the ratio of the first 4 + to 2 + energies, E(4 + )/E(2 + ) for 138 Te, with N = 86, is identical to that of 130 Te with N = 78.…”
mentioning
confidence: 99%
“…Large-scale shell model (LSSM) calculations were performed by Bianco et al [26]. The shell-model space used for the calculation included the 1g 7/2 ,2d 5/2 , 2d 3/2 , 3s 1/2 , 1h 11/2 orbitals for protons and 2f 7/2 , 3p 3/2 , 1h 9/2 , 3p 1/2 , 2f 5/2 , 1i 13/2 for neutrons.…”
Section: Comparison With Theorymentioning
confidence: 99%
“…The excitation energies, transition rates, and static moments are sensitive to shell structure, the strength of the proton-neutron interactions, and to developing collectivity [1][2][3][4][5][6][7][8][9][10]. Following the observation of an anomalously low B(E2; 0 + 1 → 2 + 1 ) by Radford et al [11], the case of 136 Te, with two protons and two neutrons outside the 132 Sn core, has been the subject of many theoretical studies, with widely varying predictions of the electromagnetic properties of the low-excitation states [1-5, 9, 10].…”
Section: Introductionmentioning
confidence: 99%